Inserción Laboral De Personas Con Discapacidad - González-González, Desireé; Gutiérrez-Barroso, Josué; González-Herrera, Ana Isabel; Márquez-Domínguez, Yolanda (European Scientific Journal, ESJ, 2017)
The aim of this study is to perform an analysis of all the variables affecting the hiring of people with Special Educational Needs. It also aims to find out the different opinions and expectations that teachers and business managers have regarding the inclusion of people with disabilities into the labour market. In this study, samples were taken both from teachers working with Special Educational Needs students and teachers from regular schools. In addition, samples from different job areas business managers were taken. It should be noted that data have also been extracted from the Instituto Nacional de Estadística (INE, National Statistics Institute) as well as from different researches and studies on the employability of people with disabilities carried out from 2012 onwards. Finally, the same methodology and procedures were established and specific questionnaires were designed for each of the samples referred to above.